2022
DOI: 10.3390/vaccines10071120
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Infectious Disease Vaccine Adjuvants

Abstract: Vaccines are one of the most significant medical interventions in the fight against infectious diseases. Since their discovery by Edward Jenner in 1796, vaccines have reduced the worldwide transmission to eradication levels of infectious diseases, including smallpox, diphtheria, hepatitis, malaria, and influenza. However, the complexity of developing safe and effective vaccines remains a barrier for combating many more infectious diseases. Immune stimulants (or adjuvants) are an indispensable factor in vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 295 publications
0
47
0
Order By: Relevance
“…Alum was not co-administered with the invading schistosome cercariae and was not expected to potentiate the humoral responses to worm-released molecules. However, increase in serum IgG2a antibodies to FhCL1 in MAP-1+MAP-2+alum-immunized mice could be related to alum co-administration [ 12 , 13 , 26 ]. Mice of this group showed the highest reduction in challenge worm burden and small intestine egg granulomas number and diameter ( Table 2 and Figs 2 and 3 ), likely because of activation of inflammatory immune cells by antibody/released gut cathepsin complexes, a mechanism of worm attrition discussed previously [ 1 , 2 , 9 ] ( Fig 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alum was not co-administered with the invading schistosome cercariae and was not expected to potentiate the humoral responses to worm-released molecules. However, increase in serum IgG2a antibodies to FhCL1 in MAP-1+MAP-2+alum-immunized mice could be related to alum co-administration [ 12 , 13 , 26 ]. Mice of this group showed the highest reduction in challenge worm burden and small intestine egg granulomas number and diameter ( Table 2 and Figs 2 and 3 ), likely because of activation of inflammatory immune cells by antibody/released gut cathepsin complexes, a mechanism of worm attrition discussed previously [ 1 , 2 , 9 ] ( Fig 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…MF59, an oil-in-water emulsion adjuvant of squalene, is as well tolerated, safe, and effective as alum, but it stimulates a greater range of macrophage activation and chemokines than alum, so that neutrophils and monocytes can be recruited for antigen presentation and transport to lymph nodes and B cells and T cells can be further activated [27]. In an experiment in Australia, it was shown that an S glycoprotein sclamp COVID-19 vaccine with MF59 as adjuvant could induce a strong immune response and stimulate S protein-specific T cell response, which had an effective protection against COVID-19 infection [28]. Therefore, MF59 has long been a candidate adjuvant for COVID-19 vaccine.…”
Section: Immune Adjuvantsmentioning
confidence: 99%
“…Virosomes are nanocarriers that mimic the structure of an enveloped virus whose nucleocapsid has been eliminated [177]. Similarly to liposomes, virosomes are an emerging lipid nanomaterial as an FDA-approved nanocarrier consisting of 60-200 nm unilamellar spherical vesicles [183]. Its preparation techniques are simple, economical, and follow similar major steps [177].…”
Section: Viral Vectors Virosomes and Plant Virus Proteinsmentioning
confidence: 99%